2020
DOI: 10.1080/15592324.2020.1752447
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics, flavonoids and antioxidant capacities inCitrusspecies with different degree of tolerance to Huanglongbing

Abstract: Huanglongbing (HLB) is a highly destructive disease to the citrus industry in Florida caused by the bacterium, Candidatus Liberibacter asiaticus(CLas) and is transmitted by Diaphorina citri. It is hypothesized that plants with high phenolic contents show higher tolerance to certain plant pathogens. In this regard, different citrus varieties and plants of genera related to Citrus were analyzed for their total phenolic and flavonoids contents, and their antioxidant capacities. In addition, the secondary metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
3
27
0
3
Order By: Relevance
“…The formation of the CTAC–phenol complex (yellow color) could also reduce the fluorescence intensity by absorbing the applied or emitted light. Our previous study showed that citrus leaves are rich in phenols and flavonoids [ 17 ]. The level of phenols and flavonoids in citrus leaves were 3–15 and 0.2–1 mg g −1 fresh weight, respectively [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of the CTAC–phenol complex (yellow color) could also reduce the fluorescence intensity by absorbing the applied or emitted light. Our previous study showed that citrus leaves are rich in phenols and flavonoids [ 17 ]. The level of phenols and flavonoids in citrus leaves were 3–15 and 0.2–1 mg g −1 fresh weight, respectively [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gallic acid and catechin were chosen as a representative for phenols and flavonoids, respectively. Gallic acid and catechin are commonly used to estimate total phenols and flavonoids in plants [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, some HLB-tolerant citrus genotypes might be superior in antioxidant mechanism or phloem regeneration. Intriguingly, it was reported that HLB-tolerant varieties contain higher levels of antioxidant capacities than the susceptible varieties 41 . ‘Sugar Belle’ mandarin, which is HLB-tolerant, has more vigorous phloem regeneration than the HLB-susceptible C. sinensis varieties 42 .…”
Section: Discussionmentioning
confidence: 99%